A gut‐centric view of aging: Do intestinal epithelial cells contribute to age‐associated microbiota changes, inflammaging, and immunosenescence?. Issue 9 (24th August 2022) - Hohman, Leah S.; Osborne, Lisa C.
Abstract: Intestinal epithelial cells (IECs) serve as both a physical and an antimicrobial barrier against the microbiota, as well as a conduit for signaling between the microbiota and systemic host immunity. As individuals age, the balance between these systems undergoes a myriad of changes due to age‐associated changes to the microbiota, IECs themselves, immunosenescence, and inflammaging. In this review, we discuss emerging data related to age‐associated loss of intestinal barrier integrity and posit that IEC dysfunction may play a central role in propagating age‐associated alterations in microbiota composition and immune homeostasis. Abstract : Age‐related comorbidities are associated with changes in the immune system, including inflammaging and immunosenesence. In this review, the authors discuss the interplay between the immune system, the microbiota, and intestinal epithelial cells. Intestinal epithelial cells remain an understudied area in the aging process, and enhanced understanding of how these cell types coordinate signals between the microbiota and the immune system may offer insights into novel strategies to promote healthy aging.